Situation analysis of implementation of the SMART safe discharge protocol: a study from East Guilan, Iran - Azar Darvishpour; Shiva Mahdavi Fashtami; Nafiseh Koochaki; Esmat Nourbakhsh Kashki (BMC Nursing)
Abstract Background Patient discharge planning is a crucial component of healthcare systems in many countries, including Iran. Despite its significance, discharge plans are often not fully implemented, and numerous challenges hinder their execution. This study aimed to explore the achievements, challenges, and solutions for implementing the SMART (Signs, Medications, Appointments, Results, Talk with me) safe discharge protocol from nurses’ perspectives. Methods This descriptive qualitative study employed purposive sampling involving 16 nurses from hospitals in eastern Guilan, northern Iran, between April and September 2024. Semi-structured and in-depth interviews were conducted until data saturation. Data analysis was performed using conventional content analysis, guided by Graneheim and Lundman’s (2004) model, utilizing MAXQDA 2007 software. To ensure trustworthiness, Lincoln and Guba’s (1985) criteria were applied. Results Data analysis revealed 46 initial codes and four main categories: “Patient and family participation in the education process”, “Comprehensive and systematic approach to education at the time of discharge”, “Challenges in implementing the safe discharge protocol”, and “Control and monitoring”. Participants reported that the SMART protocol enhances patient education from hospitalization onset, involving active patient and family participation. Although the protocol offers a more holistic and systematic approach, barriers such as incomplete discharge forms, time constraints, and ward overcrowding hinder full implementation. The effective control and supervision of head nurses and clinical supervisors are critical to ensuring the successful implementation of the protocol. Conclusions The SMART protocol has enhanced discharge education by offering a more structured approach. However, several challenges hinder its full implementation and require attention from relevant authorities to ensure more effective execution.